The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1111/j.1745-4549.1997.tb00777.x
|View full text |Cite
|
Sign up to set email alerts
|

Drying Kinetics of Red Pepper

Abstract: Desorption isotherms of unblanched and blanched red peppers were experimentally obtained at 30C. The desorption data were exploited to estimate equilibrium moisture contents of the peppers at drying temperatures other than 30C by using a semi‐empirical method. Red pepper samples were dried in a tunnel‐type drier with an air velocity of 2 m/s at 50C, 60C, 70C, and 80C. The blanched samples dried faster than the unblanched ones. The drying behavior of unblanched and blanched samples was characterized by falling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
23
3
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 10 publications
9
23
3
3
Order By: Relevance
“…The behavior of the drying rate curves (Figure 2) is in agreement with the studies of Turhan, Turhan and Sahbaz (1997), who found the constant rate period during drying of blanched chili peppers. However, the behavior observed in this study was contrary to that found by Akpinar, Bicer and Yildiz (2003), who observed that the drying of red pepper occurred only in the falling rate period at 55, 60, and 70 °C.…”
Section: Vitamin C Contentsupporting
confidence: 90%
“…The behavior of the drying rate curves (Figure 2) is in agreement with the studies of Turhan, Turhan and Sahbaz (1997), who found the constant rate period during drying of blanched chili peppers. However, the behavior observed in this study was contrary to that found by Akpinar, Bicer and Yildiz (2003), who observed that the drying of red pepper occurred only in the falling rate period at 55, 60, and 70 °C.…”
Section: Vitamin C Contentsupporting
confidence: 90%
“…This result was found to be somewhat different from the work of (Turhan et al, 1996) but such a variation could be attributed to the type of the applied drying method (tunnel drying). Diffusion coefficient (D) could be also related to the changes that occured in paprika quality during drying treatment as shown in table II.…”
contrasting
confidence: 88%
“…Drying experiments were carried out at 40 8C, 50 8C, 60 8C, 70 8C, and 80 8C. The drying apparatus and procedure were reported elsewhere [11].…”
Section: Methodsmentioning
confidence: 99%